Mechanism underlying vasorelaxation of human saphenous vein induced by procyanidin B2 - Marinko, Marija; Janković, Goran; Milojević, Predrag; Stojanović, Ivan; Nenezić, Dragoslav; Kanjuh, Vladimir; Yang, Qin; He, Guo-Wei; Novaković, Aleksandra (Archives of Pharmacy, 2022)
Findings from epidemiological studies indicate that polyphenols, widespread in human diet and with numerous biological activities, act cardioprotectively. Procyanidins are subclass of polyphenols with high content in commonly consumed foods and beverages, such as grapes, tea, chocolate, nuts and apples. Cardioprotective abilities of procyanidins, might, at least partly, attribute to their vasodilator properties. Since exact mechanisms of procyanidin B2-induced vasorelaxation are unknown, our study aimed to investigate relaxant effect of procyanidin B2 on isolated human saphenous vein (HSV) and its underlying mechanisms. Discarded segments of HSV were collected from patients undergoing bypass surgery and studied in organ baths. Procyanidin B2 caused concentration-dependent relaxation of HSV precontracted by phenylephrine. The relaxation was strongly affected by inhibitors of NO/cGMP pathway, L-NAME, hydroxocobalamin and ODQ. Indomethacin, a cyclooxygenase inhibitor, significantly reduced only relaxation produced by the highest concentrations of procyanidin B2. Combination of apamin and TRAM-34, selective blockers of small- and intermediate-conductance Ca2+-activated K+ (KCa) channels (SKCa and IKCa), in the presence of L-NAME and indomethacin, did not additionally affect procyanidin B2-induced relaxation. Additionally, relaxation induced by procyanidin B2 was partially attenuated by 4-aminopyridine, predominant blocker of voltage-gated K+ (KV) channels, significantly inhibited by glibenclamide, selective ATP-sensitive K+ (KATP) channels inhibitor, and almost abolished by iberiotoxin, highly selective blocker of large-conductance KCa (BKCa). Our results revealed that procyanidin B2 acts as a potent vasodilator on isolated human venous graft. Mechanism of this relaxation of HSV probably involves stimulation of NO production, as well K+ channels opening, especially BKCa, and partially KATP and KV.